Exploring Possible Triangle Singularities in the Ξ b − → K − J / ψ Λ Decay - Chao-Wei Shen (Symmetry, 2020)
We analyze possible singularities in the <semantics>J/ψΛ</semantics> invariant mass distribution of the <semantics><msubsup>Ξb−</msubsup><mspace width="3.33333pt"></mspace>→<mspace width="3.33333pt"></mspace>K−J/ψΛ</semantics> process via triangle loop diagrams. Triangle singularities in the physical region are found in 18 different triangle loop diagrams. Among those with <semantics>Ξ*</semantics>-charmonium-<semantics>Λ</semantics> intermediate states, the one from the <semantics>χc1Ξ(2120)Λ</semantics> loop, which is located around 4628 MeV, is found the most likely to cause observable effects. One needs S- and P-waves in <semantics>χc1Λ</semantics> and <semantics>J/ψΛ</semantics> systems, respectively, when the quantum numbers of these systems are <semantics>1/2+</semantics> or <semantics>3/2+</semantics>. When the quantum numbers of the <semantics>Ξ(2120)</semantics> are <semantics>JP=1/2+</semantics>, <semantics>1/2−</semantics> or <semantics>3/2+</semantics>, the peak structure should be sharper than the other <semantics>JP</semantics> choices. This suggests that although the whole strength is unknown, we should pay attention to the contributions from the <semantics>Ξ*</semantics>-charmonium-<semantics>Λ</semantics> triangle diagram if structures are observed in the <semantics>J/ψΛ</semantics> invariant mass spectrum experimentally. In addition, a few triangle diagrams with the <semantics><msubsup>Ds1*</msubsup>(2700)</semantics> as one of the intermediate particles can also produce singularities in the <semantics>J/ψΛ</semantics> distribution, but at higher energies above 4.9 GeV.